2009
DOI: 10.1111/j.1538-7836.2009.03477.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‐induced platelet cytotoxicity: a new contributory factor for doxorubicin‐mediated thrombocytopenia

Abstract: We demonstrated that DOX can directly induce platelet cytotoxicity through ROS generation, decreased glutathione levels, and protein thiol depletion. We believe that this study provides important evidence for the role of DOX-induced platelet cytotoxicity in the development of thrombocytopenia in DOX-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
(47 reference statements)
1
44
1
Order By: Relevance
“…It enables real-time detection of treatment-induced complications in the same animal over an extended period of time. We evaluated two classes of chemotherapies: doxorubicin which is known to be toxic to endothelial cells in vitro as well as in tissues obtained from animals treated with doxorubicin [10][11][12][13][14][15] , and paclitaxel as a control chemotherapy for which the former evidence for any vascular effect is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…It enables real-time detection of treatment-induced complications in the same animal over an extended period of time. We evaluated two classes of chemotherapies: doxorubicin which is known to be toxic to endothelial cells in vitro as well as in tissues obtained from animals treated with doxorubicin [10][11][12][13][14][15] , and paclitaxel as a control chemotherapy for which the former evidence for any vascular effect is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…LdH has an important role in the energy metabolism of platelets, so its inhibition or leakage as in the case of doxorubicin can be cytotoxic to platelets [14]. Ketoprofen has its efficacy established as an anti-inflammatory and analgesic agent [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…14 Observations of Kim et al 15 have found that doxorubicin can induce procoagulant activity; and what is more, ROS production is involved in this process. Moreover, results of Kim et al 15 showed that doxorubicin can induce cytotoxicity in blood platelets through ROS generation and also decrease glutathione or protein thiol levels. Increased complication of thrombotic disorders is well documented in cancer patients treated with other ROS-generating chemotherapeutic drugs (bleomycin or cisplatin).…”
Section: Oxidative Stress In Breast Cancermentioning
confidence: 96%
“…[7][8][9][10][11][12][13] ROS produced during cancer chemotherapy are often a source of serious side effects (cardiotoxicity, nephrotoxicity, ototoxicity, and hematological toxicity). 14,15 The oxidative stress, detected by using various biomarkers (including the level of carbonyl groups and 3-nitrotyrosine in proteins, the total antioxidant level (TAS), the activity of antioxidative enzymes), had been observed in breast cancer patients before and during different phases of treatment. [7][8][9][10][11][12][13][16][17][18][19][20][21][22][23] Results of Kedzierska et al 11 have shown that the total level of glutathione (an important physiological antioxidant) in plasma isolated from breast cancer patients (before and during treatment, during different phases of chemotherapy (doxorubicin and cyclophosphamide)) was lower than in healthy persons.…”
Section: Oxidative Stress In Breast Cancermentioning
confidence: 99%